ANALYSIS OF DIFFICULTIES IN LEARNING MATHEMATICS IN ELEMENTARY SCHOOL - Gamar Al Haddar; Eliza Novianti (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2019)
Mathematics is a way to solve problems in daily life so that it is necessary to be mastered. However most of students still believe that mathematics is difficult lesson to learn. Relating to this issue, the researcher conducted a qualitative research to describe the difficulties encountered by students when learning Mathematics. To collect the data, the researcher applied observation, interview, and documentation. The data was then analyzed through data reduction, data display and conclusion. Having analyzed the data, it can be concluded that students’ difficulties in learning Mathematics came from teacher’s techniques in explaining the lesson, inadequate school’s facilities and infrastructure, family environment, and curriculum. Hence, it is suggested to teachers to apply teaching techniques based on theory of mathematics learning, and enriched with learning aids to encourage students’ motivation and positive attitude. In addition, the parents are expected to pay more attention to students’ learning development especially on learning difficulties of learning mathematics by cooperating with the teachers.